Understanding metal–organic frameworks for photocatalytic solar fuel production. Issue 29 (15th February 2017) - Santaclara, J. G.; Kapteijn, F.; Gascon, J.; van der Veen, M. A.
Abstract : The fascinating chemical and physical properties of MOFs have recently stimulated exploration of their application for photocatalysis. Design guidelines for these materials in photocatalytic solar fuel generation can be developed by applying the right spectroscopic tools. Abstract : The fascinating chemical and physical properties of MOFs have recently stimulated exploration of their application for photocatalysis. Despite the intense research effort, the efficiency of most photocatalytic MOFs for solar fuel generation is still very modest. In this highlight we analyse the current status of the field and stress the potential of advanced spectroscopic techniques to gain structural and mechanistic insight and hence support the future development of MOFs to harvest and store solar energy.